A Response to Michael Spitzer's Commentary - Lahdelma, Imre; Eerola, Tuomas (Empirical Musicology Review, 2020)
The authors respond to the commentary by Michael Spitzer which appeared in Vol. 14, No. 1-2 of Empirical Musicology Review. The response 1) points out the problem with equating nostalgia and tension in the perception of single chords, 2) makes a case for why studying the role of vertical harmony, isolated from other musical cues, is insightful, and 3) questions the relevance of appoggiaturas as an explanation for the perception of nostalgia in single chords.